Pectinase production by Penicillium viridicatum RFC3 by solid state fermentation using agricultural wastes and agro-industrial by-products - Silva, D.; Martins, E. S.; Silva, R. da; Gomes, E. (Springer, 2002)
Pectin lyase and polygalacturonase production by newly isolated Penicillium viridicatum strain Rfc3 was carried out by means of solid state fermentation using orange bagasse, corn tegument, wheat bran and mango and banana peels as carbon sources. The maximal activity value of polygalacturonase (Pg) (30U.g(-1)) was obtained using wheat bran as carbon source while maximal pectin lyase (Pl) (2000 U.g(-1)) activity value was obtained in medium composed of orange bagasse. Mixtures of banana or mango peels with sugar cane bagasse resulted in increased Pg and Pl production compared to fermentations in which this residue was not used. ne mixture of orange bagasse and wheat bran (50%) increased the production of Pg and Pl to 55 U.g(-1) and 3540 U.g(-1) respectively. Fractions of Pg and Pl, isolated by gel filtration in Sephadex G50, presented optimum activity at pH 5.0 and 10.5 respectively. Maximal activity of Pg and PI fractions was determined at 55degreesC and 50degreesC respectively. Pg was stable in neutral pH range and at 40degreesC whereas Pl was stable in acidic pH and at 35degreesC, for 1 h.
Keywords: Penicillium viridicatum; polygalacturonase; pectin lyase; wastes; by-product